Bahasa Inggris - Siti Aisyah; Dwi Harjanti (LP2M IAIN Sultan Amai Gorontalo, 2020)
A good quality of translation is known by assessing it. One way to assess translation product is by assessing the naturalness. This research aims at describing the naturalness of translation in J. K. Rowling’s Harry Potter and the Half Blood Prince novel into Indonesian version Harry Potter dan Pangeran Berdarah Campuran. This is a descriptive qualitative research. The data were sentences in the original novel and its Indonesian translation. The data were collected using content analysis technique and analyzed using Larson theory of naturalness in translation and supported by other theories. This research does not mean to judge the translator but it is intended to give contribution to the development of translation by analyzing the naturalness of the translation. The finding showed that there are four levels of naturalness found in the translation of the novel, such as (1) highly natural (171 data or 78.1 %), (2) natural (33 data or 15.1 %), (3) less natural (13 data or 5.9 %), and (4) unnatural (2 data or 0.9 %).